Development of a touch sensing system for human-robot interaction - Prawira, Ivan Nata (2019)
In the past few decades, industrial robots have been increasingly and rapidly used in many industries. With today’s advancements in technology, it is almost certain that robotics will be gradually taking over various industries, especially in manufacturing industry. This paper will discuss about the safety issues regarding a Human Robot Interaction (HRI) in the same working space after briefly introducing about industrial robots. The project conducted will experiment on a new anti-collision function that can be implemented to pre-owned industrial robots. Under normal circumstances, introduction of such new functions requires the repurchase of a brand-new robot which is extremely costly. However, this paper proposes a function that acts as an add-on component that can be easily attached to any robots. With this addition, the robot will be able to detect and respond instantly whenever a contact by any humans is detected. This paper elaborated on how this function is applied to a commonly used industrial robot, the SCARA robot.